An Automation System Design for Dough Kneaders and Dosing Machines with Microprocessor Based and 5 Flows - Hasbi APAYDIN; Şükrü KİTİŞ (International Journal of Applied Methods in Electronics and Computers, 2015)
In this study, an automation system is designed for bakeries, biscuit factories, flour and bakery products used dough kneading and dosing machines. This microprocessor-based design, made of 5-flowing flour and water dispensing operation. For this, the area is very easy to become available and can be programmed PIC16F877A microcontroller used. This automation system isn’t used in most of the plants and mixing ratios. Therefore the operator’s ability and speed very important for mixing ratios and the production rate without automation system. This is quite a challenge, raw material and leads to a loss of time. This study, carried out the difficulties that emerged from the automation system can be provided at low cost and hassle-free.